Re-centering women in tourism : anti-colonial feminist studies - Riemer, Frances Julia, 1955-; Babb, Florence E. (Anthropology of tourism: heritage, mobility, and society., 2023)
Re-Centering Women in Tourism addresses tourism as simultaneously empowering women and reproducing colonial hierarchies. By centering women's multivalent lived experiences in tourism projects, this collection reframes the very presuppositions on which tourism initiatives are based and helps imagine sustainable and regenerative alternatives.